Informal Sector Self-Employed Workers’ Old Age Pension Scheme in Retail Sector in Zimbabwe - Makochekanwa, Albert; Cheure, Cheure; Chundu, Moses; Mavodyo, Elisha (Journal of Social Development Studies, 2024)
The high incidence of informality in Zimbabwe implies that a large proportion of the adult population does not have access to contributory pension schemes during their working lives, rendering them ineligible for old-age pensions. The primary goal of this research is to develop a pragmatic informal retail sector noncontributory old-age pension scheme in Zimbabwe. The study drew empirical evidence from a comprehensive countrywide study using mixed-methods research. The study concluded that several factors, including the respondents' demographic characteristics, are important considerations in developing an effective non-contributory old-age informal sector pension scheme. Based on the study's findings, the study proposes alternative non-contributory old-age informal sector pension schemes, such as financing the non-contributory old-age social pension, determining the monthly amount of a non-contributory old-age pension, and gradually covering a non-contributory old-age pension gap. The study recommends the introduction of a non-contributory informal sector retirement pension fully funded by the government. Keywords: retail informal sector old-age pension scheme; social security; informal sector; Zimbabwe.